POLA SEGREGASI DAN HERITABILITAS SIFAT KETAHANAN KEDELAI TERHADAP COWPEA MILD MOTTLE VIRUS POPULASI WILIS X MLG2521 - Maimun Barmawi . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2007)
Segregation and Heritability of Cowpea Mild Mottle Virus Resistant Characters of Soybean Genotypes from Crosses Between Wilis and Mlg2521 Population. This research was conducted within July to October, 2005 at experiment station of Lampung University. The aims of this research were to evaluate the segreation and heritability of resitant characters at F2 population of Wilis x Mlg2521. The result showed that segregation of resistant characters segretate 13:3 of succeptible and resistant genotypes. Heritability in the narrow sense based on disease severity was 13,18% (low) and heritabilitas heritability in the broad-sense was 80,91% (high).